2007
DOI: 10.1007/s11095-007-9290-8
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Proliferation and Erythroid Differentiation of K562 Cells by siRNA-induced Depression of OCTN1 (SLC22A4) Transporter Gene

Abstract: It was suggested that OCTN1 is involved in the transport of physiological compounds that are important for cell proliferation and erythroid differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…[9][10][11] Furthermore, we previously suggested that OCTN1 is expressed preferentially in erythroid cells. 7,8) Accordingly, OCTN1 is considered to be a physiologically important transporter in several cells such as blood cells, whereas its physiological roles remain to be clarified. As substrates of OCTN1, organic cations such as TEA and carnitine were demonstrated considering from the closely related transporter family members such as organic cation transporters OCTs and carnitine transporter OCTN2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] Furthermore, we previously suggested that OCTN1 is expressed preferentially in erythroid cells. 7,8) Accordingly, OCTN1 is considered to be a physiologically important transporter in several cells such as blood cells, whereas its physiological roles remain to be clarified. As substrates of OCTN1, organic cations such as TEA and carnitine were demonstrated considering from the closely related transporter family members such as organic cation transporters OCTs and carnitine transporter OCTN2.…”
Section: Discussionmentioning
confidence: 99%
“…creased apoptosis in K562 cells was associated with the suppressed expression of human OCTN1 with siRNA method. 8) Accordingly, we hypothesized that the OCTN1-mediated uptake of ergothioneine is important in protective function against oxidative damage and rat Octn1 may be involved in the uptake of the anti-oxidant by PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In peripheral organs, OCTN1 has been proposed to be involved in proliferation and differentiation of erythroid cells (Nakamura et al, 2007), and to be associated with 6 development of rheumatoid arthritis (Tokuhiro et al, 2003) and Crohn's disease .…”
Section: Introductionmentioning
confidence: 99%
“…Since ET is suggested to inhibit apoptosis,6 7 an increased tissue accumulation in 503F carriers may contribute to a defective innate immunity by prolonging inflammatory immune cell survival or by impairing removal of intracellular bacteria.…”
mentioning
confidence: 99%